1996
DOI: 10.1143/jjap.35.5196
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect on the Phase Transition in PbTiO3 Fine Particles

Abstract: The finite size effect on the phase transition in PbTiO3 fine particles is described. Very small crystals with an average diameter of 14.2 nm were obtained by lowering the calcination temperature to 400° C. Raman scattering measurements of such fine particles were carried out to study the dependence of the phase transition temperature on the particle size. The X-ray diffraction pattern was also measured to study the tetragonality, c/a ratio. The results strongly suggest the presence of a critical size below w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 11 publications
2
34
1
Order By: Relevance
“…According to the literature, one would not expect to see a significantly reduced T C until the grain size decreases down to about 20 nm. 23 This is in clear contrast to the microstructure in our nanocomposite.…”
contrasting
confidence: 63%
“…According to the literature, one would not expect to see a significantly reduced T C until the grain size decreases down to about 20 nm. 23 This is in clear contrast to the microstructure in our nanocomposite.…”
contrasting
confidence: 63%
“…The growth temperature and pressure were 540-600 o C and 5.0Torr, respectively. (C 2 H 5 ) 3 PbO-n-CH 2 C(CH 3 ) 3 , Ti(O-i-C 3 H 7 ) 4 and O 2 were used as precursors and oxidant, respectively [13][14][15]. The surface morphology and piezoelectric properties were evaluated by atomic force microscopy (AFM) and piezoresponse force microscopy (PFM).…”
Section: Methodsmentioning
confidence: 99%
“…The size dependence was considered as extrinsic size effects derived from the clamping by substrates and 90 o domain wall movements [1][2][3]. Intrinsic size effects, in these reports, were not observed because the dimensions of islands fabricated by the top down methods were much larger than the size in which intrinsic size effects were observed in ultrafine particles [4][5][6]. On the other hand, ferroelectric islands with dimensions similar to the critical size of ultrafine particles have been successfully fabricated by the bottom up method [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles, have 90 been widely investigated by researchers. 29,141,142,227 For example, the finite size-effect on the ferroelectric phase transitions in PbTiO3 nanoparticles were studied in the late '80s.…”
Section: Scaling Effects Of Nanoscale Ferroelectric Materialsmentioning
confidence: 99%
“…29,141,142 Park et al 29 first reported the decrease in TC and the increase in the tetragonal crystal 25 distortion of BaTiO3 nanoparticles with decreasing diameter (33 to 140 nm). The researchers also determined that the minimum critical diameter required for a ferroelectric phase transition in the nanoparticles was 37 nm.…”
mentioning
confidence: 99%